TOXIC EFFECT OF ETHANOL ON MUCOUS MEMBRANES - Yeroshenko, G.A.; Shevchenko, K.V.; Kazakova, K.S. (World of Medicine and Biology, 2017)
According to the World Health Organization, 3.3 million deaths occur every year in the world as a result of harmful use of alcohol, accounting for 5.9% of all deaths. Harmful use of alcohol is the causative factor for more than 200 health disorders associated with illness and injury. According to modern scientific concepts, dependence on alcohol is often accompanied by various changes in the oral cavity. Many authors note various changes in the dental status with alcohol abuse, especially in persons with liver and gastrointestinal tract damage. A number of studies of scientists say that ethanol is a risk factor for cancer of the oral mucosa.
Keywords: ethanol; mucous membranes; toxic effect